Characterization in inl+ transformants of Neurospora crassa obtained with a recombinant cosmid-pool - Zs. Feher; M. Schablik; A. Kiss; A. Zsindely; G. Szabo (Fungal Genetics Reports, 1985)
Characterization in inl+ transformants of Neurospora crassa obtained with a recombinant cosmid-pool